Post‐Assembly Photomasking of Potassium Acyltrifluoroborates (KATs) for Two‐Photon 3D Patterning of PEG‐Hydrogels. Issue 11 (20th October 2020) - Song, Haewon; Wu, Dino; Mazunin, Dimitry; Liu, Sizhou M.; Sato, Yoshikatsu; Broguiere, Nicolas; Zenobi‐Wong, Marcy; Bode, Jeffrey W.
Abstract: Chemical ligation reactions of functional groups that can be masked with two‐photon labile protecting groups provide a powerful technology for the three‐dimensional patterning of molecules – including proteins – onto hydrogel scaffolds. In order to utilize readily prepared hydrogels constructed by the potassium acyltrifluoroborate (KAT)‐hydroxylamine amide formation ligation for two‐photon patterning, we have developed a unique post‐polymerization protecting group strategy through the reaction of KATs and dithiols in water and deprotection by two‐photon excitation. After precise 3D spatially confined light irradiation, the unprotected KATs undergo ligations with hydroxylamine‐functionalized superfolder GFP and sulforhodamine B for the composition of three‐dimensional patterns. Abstract :